2018
DOI: 10.18820/2519593x/pie.v36i1.6
|View full text |Cite
|
Sign up to set email alerts
|

The lack of parent involvement as hindrance in selected public primary schools in South Africa: The voices of educators

Abstract: Although parent involvement is fundamental for school functioning, the nature and extent of such involvement is debatable and contested amongst stakeholders. A qualitative based study under pinned by the interpretive paradigm was undertaken to explore the voices of educators regarding parent noninvolvement and its implications for learner experiences and performance in a disadvantaged community in South Africa. Data was gathered through individual and focus group interviews, involving 3 principals and 12 teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 27 publications
2
39
1
Order By: Relevance
“…This practice affects the pupils learning experiences at school, which in turn, exposes them to inferior education leading to poor academic performances in school. Similarly, scholars such as Ushie, Emeka, Ononga, and Owolabi (2012), and Munje and Mncube (2018) argued that the higher the level of interest of the parents in the children's education, the better the level of children learning success.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This practice affects the pupils learning experiences at school, which in turn, exposes them to inferior education leading to poor academic performances in school. Similarly, scholars such as Ushie, Emeka, Ononga, and Owolabi (2012), and Munje and Mncube (2018) argued that the higher the level of interest of the parents in the children's education, the better the level of children learning success.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Given that a significant proportion of parents in South Africa, and other low-income countries, are often poor and may be functionally illiterate (Matshe 2014), low levels of parental involvement in education are to be expected. Despite the argument that some poor parents have legitimate reasons for not applying themselves adequately in their children's education (Abrahams 2013), there is a view that teachers in South African public schools are also not doing much to engage parents and support their participation (Munje & Mncube 2018).…”
Section: School and Teacher-driven Initiatives To Involve Parentsmentioning
confidence: 99%
“…Yet, research by Mathwasa and Okeke (2016:235) in South Africa showed that FP teachers' often negative 'attitude towards fathers prevented them from inviting fathers to partake in the education of their children'. Also, it should be noted that South African male caregivers often experience numerous barriers to their involvement in the educational processes of learners in FP, including a lack of education (Munje & Mncube 2018), factors such as financial difficulties forcing them to seek employment far from their families (Mavungu 2013) and feelings of shame and inadequacy because of unemployment (Rabe 2018). However, research indicates that FP teachers often overlook such barriers and inadvertently perceive male caregivers as not showing interest in their children's education (Mathwasa & Okeke 2016;Munje & Mncube 2018).…”
Section: School and Teacher-driven Initiatives To Involve Parentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Learners' social and emotional development, as well as their academic performance, can directly be linked to the level of effective parental involvement. According to Munje and Mncube (2018), despite the existence of various policies and acts (namely the South African School's Act, 84 of 1996) to improve and encourage relationships between the school and parents, there is still an ongoing low level of parental involvement in South African schools.…”
Section: Introductionmentioning
confidence: 99%